ISEAS Perspective : Watching the Indonesian Elections 2014. - Fionna, Ulla (Institute of Southeast Asian Studies, 2015)
"As the euphoria fades from the Jokowi presidency, this timely book reviews the processes that brought him to the top, and the processes that have undermined his initial standing. The nineteen articles by ten writers provide views from along the way, starting with a chapter on the Jakarta governor elections from November 2012 and preceding through the key events up to a contemporary assessment in February 2015. Several major clues to the current disillusion are provided in accounts of the legislative elections and the presidential campaigns. Key topics are vote buying, the Islamic factor, econ.